How frequent is nocturia in medical students? - Coskun, Burhan; Yurdakul, Turgut; Kaygisiz, Onur; Koca, Nizameddin; Yavascaoglu, İsmet (The European Research Journal, 2017)
Objective. Nocturia is the most common lower urinary tract symptom and its prevalence increases with age. The frequency of nocturia and related bother are not widely investigated in young adults in the literature. In this study we aimed to investigate frequency, bothersome and relation of nocturia with anxiety in medical students. Methods. A questionnaire consisting of 19 items were sent to medical students via social media by using Survey MonkeyTM software. Questions include demographic characteristics, fluid intake habits, voiding symptoms, and bother score related to nocturia. Also, Beck Anxiety Inventory was used to measure level of anxiety. Results. A total of 221 students replied the survey. The mean age was 20.7±2.10. Forty-seven (21.3%) students had nocturia. The rate of nocturia was 27.4% and 13.4% in women and men, respectively (p=0.011). The frequency of nocturia per night was 80.2%, 17.3% and 2.2% (1, 2, 3 times; respectively). While the frequency of nocturia was found to be related with bother scores there were no relation of gender with degree of bother. Conclusion. Nocturia is frequent in medical students, especially in women. Commonly, nocturia do not cause bother in young adults with one episode and it is not related with anxiety.